A student solves the following problem:
Problem:
2(x−3) + 3x = 19
Step 1: 2x − 6 + 3x = 19
Step2: (2x + 3x) −6 = 19
Step 3: 5x − 6 = 19
Step 4: 5x −6 + 6 = 19 + 6
Step 5: 5x = 25
Step 6: x = 5
What property justifies going from step 3 to step 4?
(1 point)
Responses
Commutative Property of Addition
Commutative Property of Addition
Addition Property of Equality
Addition Property of Equality
Distributive Property
Distributive Property
Combine Like Terms
Combine Like Terms
Substitution Property
Substitution Property
1 answer
The property that justifies going from step 3 to step 4 is the Addition Property of Equality.